2015
DOI: 10.1093/ejcts/ezv185
|View full text |Cite
|
Sign up to set email alerts
|

Aortic valve repair for insufficiency in older children offers unpredictable durability that may not be advantageous over a primary Ross operation

Abstract: OBJECTIVES:To evaluate the durability of aortic valve (AoV) repair relative to other strategies for children with significant aortic insufficiency (AI). METHODS:From 2001 to 2012, 90 children with greater than or equal to moderate AI underwent surgery. Resulting procedures were classified according to final operative outcome: AoV repair (repair; n = 46, 51%), Ross procedure (Ross; n = 21, 23%) or replacement with mechanical or tissue prosthesis [aortic valve replacement (AVR); n = 23, 26%]. Repeated measures (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 18 publications
1
9
0
2
Order By: Relevance
“…This is an exceptional imaging tool which yields high-quality images and allows essential preoperative planning for transcatheter aortic valve replacement (TAVR) [23]. Although TAVR is not routinely used in the paediatric population, a study conducted in 2019 found this method of valve replacement to be a reasonable alternative to surgical aortic valve replacement in certain paediatric patients with suboptimal predicted surgical outcomes [24]. Furthermore, CCT may aid in characterising aortopathy in patients with inconclusive echocardiography findings [16].…”
Section: Cardiac Computed Tomography (Cct)mentioning
confidence: 99%
See 2 more Smart Citations
“…This is an exceptional imaging tool which yields high-quality images and allows essential preoperative planning for transcatheter aortic valve replacement (TAVR) [23]. Although TAVR is not routinely used in the paediatric population, a study conducted in 2019 found this method of valve replacement to be a reasonable alternative to surgical aortic valve replacement in certain paediatric patients with suboptimal predicted surgical outcomes [24]. Furthermore, CCT may aid in characterising aortopathy in patients with inconclusive echocardiography findings [16].…”
Section: Cardiac Computed Tomography (Cct)mentioning
confidence: 99%
“…CMR and 4D flow MRI provide robust data on patientspecific aortic haemodynamics [24][25][26]. This helps to predict risk of disease progression, particularly in BAV20.…”
Section: Cardiac Magnetic Resonance (Cmr)mentioning
confidence: 99%
See 1 more Smart Citation
“…В результате пациенты, у которых не применяли аугментацию створки АК, демонстрировали лучшую свободу от реопераций. В поддержку этой гипотезы говорят также результаты Wilder TS, et al, которые получили практически 50% реопераций у детей старше 1 года, которым применялась данная методика РеАК со средним периодом времени до повторного вмеша-тельства 4,4 года, что перекликается с нашими данными [14].…”
Section: таблица 3 сравнительная характеристика дооперационных показаunclassified
“…Дефицитная ткань часто имеет предпосылку к выполнению таких методик, как комиссуротомия в сочетании со швом Trusler, рафе "шейвинг", аугментацией створок. Согласно данным Wilder TS, et al, помимо преимущественного применения такой методики, как аугментация створок, некоторым пациентам была выполнена комиссуротомия в комбинации со швом Trusler [14]. Однако пликация свободного края створок или триангулярная резекция не была применена, что свидетельствует об исходно плохом качестве, количественном дефиците створок, в результате чего получен субоптимальный результат, который перекликается с нашими данными.…”
Section: таблица 3 сравнительная характеристика дооперационных показаunclassified